Impact of contract farming of paddy seed on smallholder farm profits: evidence from Nepal - Anjani Kumar; Devesh Roy; P K Joshi; Gaurav Tripathi; Rajendra P Adhikari (Agricultural Economics Research Review, 2023)
The paper identifies determinants of farmers’ participation in contract farming of paddy seed and its impact on farm income using survey data from 502 farmers engaged in paddy seed production in Nepal. The results show that contract farming enhances profits for paddy seed cultivators and participation in it is influenced by farm size and main occupation of the cultivators. The empirical evidence on benefits from contract farming suggest the need for conducive policies for promotion and upscaling of contract farming for augmenting seed production.